Structural Modification of Sol-Gel Synthesized V2O5 and TiO2 Thin Films with/without Erbium Doping - Fatma Pınar Gökdemir; Ayşe Evrim Saatci; Orhan Özdemir; Kubilay Kutlu (Advances in Materials Science and Engineering)
Comparative work of with/without erbium- (Er-) doped vanadium pentoxide (V2O5) and titanium dioxide (TiO2) thin films were carried out via sol-gel technique by dissolving erbium (III) nitrate pentahydrate (Er(NO3)3·5H2O) in vanadium (V) oxoisopropoxide (OV[OCH(CH3)2]3) and titanium (IV) isopropoxide (Ti[OCH(CH3)2]4). Effect of Er doping was traced by Fourier transform IR (FTIR), thermogravimetric/differential thermal (TG/DTA), and photoluminescence measurements. UV-Vis transmission/absorption measurement indicated a blue shift upon Er doping in V2O5 film due to the softening of V=O bond while appearance of typical absorption peaks in Er-doped TiO2 film. Granule size of the films increased (reduced) upon Er substitution on host material compared to undoped V2O5 and TiO2 films, respectively.